2012
DOI: 10.1007/jhep05(2012)048
|View full text |Cite
|
Sign up to set email alerts
|

Minimal flavour violation and neutrino masses without R-parity

Abstract: Abstract:We study the extension of the Minimal Flavour Violation (MFV) hypothesis to the MSSM without R-parity. The novelty of our approach lies in the observation that supersymmetry enhances the global symmetry of the kinetic term and in the fact that we consider as irreducible sources of the flavour symmetry breaking all the couplings of the superpotential including the R-parity violating ones. If R-parity violation is responsible for neutrino masses, our setup can be seen as an extension of MFV to the lepto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…There are three notable works on the application of the MFV hypothesis within the context of supersymmetric SM with R-parity violation [121,42,122]. Recall, there are three R-parity violating operators in the superpotential that can be written down if one wants to accommodate the minimal fermionic field content of the SM.…”
Section: Flavor Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three notable works on the application of the MFV hypothesis within the context of supersymmetric SM with R-parity violation [121,42,122]. Recall, there are three R-parity violating operators in the superpotential that can be written down if one wants to accommodate the minimal fermionic field content of the SM.…”
Section: Flavor Modelsmentioning
confidence: 99%
“…The easiest way to prevent this from happening is to forbid all of these terms using R-parity. It has also been demonstrated that it is possible to suppress B and L violation to the extent that there is no problem with proton decay even if one does not demand strict R-parity conservation but instead resorts to the MFV hypothesis [121,42,122]. The authors of Refs.…”
Section: Flavor Modelsmentioning
confidence: 99%
“…An analysis of MFV supersymmetry with this symmetry group is performed in [53]. In this section, we will take the horizontal symmetry as a diagonal subgroup of SUð3Þ 5 , in order to compare our approach to the MFV approaches based on Uð3Þ 5 [17,18].…”
Section: Suð3þ 5 Embedding Of the Horizontal Symmetrymentioning
confidence: 99%
“…[52][53][54][55][56] this criterion has been rigorously defined in terms of continuous flavour symmetries, considering an effective operator description in the SM context. Even if the MFV ansatz is successful to prevent large flavour violation also in models beyond SM [57][58][59][60][61][62][63], it does not provide any explanation for the origin of fermion masses and mixings. From this the idea that the MFV is a too restrictive context to provide any clue on the origin of masses.…”
Section: Introductionmentioning
confidence: 99%